Establishing Cluster Policy as the Instrument for Competitive Recovery of Biotechnological Industry - SHCHINOVA, Raisa; SUVOROVA, Larisa; ZAUSHITSYNA, Lilia (Journal of Advanced Research in Law and Economics; Vol 7 No 8 (2016): JARLE Volume VII, Issue 8(22), Winter 2016, 2017)
Today the adaptation of the ‘cluster policy’ concept to the specific conditions of functioning of government, science, education, business and community can be observed in Russia. The necessity for establishing and realization of the cluster policy, its efficiency and its contribution to the development of the high-tech industry and the regions of Russia are discussed in this paper. The authors consider the cluster policy to be an efficient alternative to the traditional ‘industry-based policy’ carried out in the depressive regions of Russia. The authors think of the cluster policy as collaborative, purposeful, documented actions of the representatives of government, business, educational and research institutes, as well as other members of cluster, aimed to establish supportive business environment for future development of a cluster and improvement of the performance effectiveness of all its members. The need for establishing regional cluster policy and creation of cluster-based strategy of development of the Kirov region, aimed to competitive recovery of the advanced innovative economic sectors of the region (biotechnology and pharmaceuticals), is justified in this paper on the basis of the analysis of the investment potential and activity. Considering the specific features of local development, the aims and principles of the regional cluster policy were determined and the Cluster strategy program of the Kirov region, the stages of its realization, the objectives and responsible officers were assigned. The authors determined the levels of establishing and realization of the cluster policy in the Kirov region according to the experience of the cluster policy implementation in Russia. The role of the Cluster Development Center of the Kirov region as the main coordinator of the projects, providing the development of the innovative technological clusters and the collaboration of the cluster members of the region, was discussed as part of the realization of the cluster policy. According to the results of the investigation of current situation in the realization of the cluster policy in the Kirov region, the authors revealed certain high-priority tasks, requiring immediate actions of the local government. The results of our analysis bring us to the conclusion that the implementation of the cluster development strategy in the Kirov region will promote the increase in the competitive capacity of the economic entities included in the regional innovative technological clusters.